Case Report: Jet lag and travel fatigue effects on performance in a world-class Paralympic shot-putter after eastward long-haul transmeridian travel - Garcia-Carrillo, E.; Thapa, R. K.; Hermosilla-Palma, F.; Alarcón-Rivera, M.; Farías-Valenzuela, C.; Azócar-Gallardo, J.; Yáñez-Sepúlveda, R.; Olivares-Arancibia, J.; Castillo-Paredes, A.; Calleja-González, J.; Judge, L. W.; Fuentes-Barría, H.; et al. (Frontiers in Sports and Active Living, 2026)
Introduction: This case report aimed to examine the effects of long-haul eastward transmeridian travel on neuromuscular performance, subjective well-being, and internal training load in a World-class female Paralympic shot-putter preparing for the Paris 2024 Paralympic Games.